Student enrolment system for PTPL college - Azizah, Jamel; Fatma Syazwani, Mohamad; Liza, Maten (Universiti Malaysia Sarawak (UNIMAS), 2004)
Year by year, the world fast growing with modernization of Information Technology, many implementations of which has been brought up in processing data. The new technologies have brought up the environment to develop new system each year. People get established knowledge and know more in using any computerized system. The implementation of Student Enrolment System for PTPL College is based on Visual Basic interface that integrates with Microsoft Access database platform. It is developed to meet the organization's requirements. This system will function mainly to register student's information and subjects taken. In students' registration information, administrator can add, view, modify and delete student's information in easy way and more secured. In subject registration, administrator also can register students' subject registration according to the subject requirements in each semester. Therefore, the students have to register their information and subjects by manually (i.e., filling the form). Student Enrolment System is implemented to make filing system more systematic and secured.